Computermediets differentieringspotentiale i sproglig læring belyst ud fra en procesorienteret synsvinkel - Ambjørn, Lone (HERMES - Journal of Language and Communication in Business, 2003)
The main point of this article is to demonstrate that the existence of the computer-medium within L21 learning and acquisition is justified by its potential of differentiation. In order to make the optimum use of this potential, it is necessary to design syllabi based on L2 research and theories of language learning acquisition. Taking as a starting point the learner’s interlanguage development, I am introducing a model of L2 learning and acquisition, a model based on input as well as on output. The strong point in having this model is that you can use it for computer-assisted language learning, and in this way you can contribute to the implementation of differentiated syllabi that take into account the psycholinguistic processes that characterize interlanguage development.